2017
DOI: 10.1111/jspn.12177
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between food insecurity, child weight status, and parent‐reported child eating and snacking behaviors

Abstract: Purpose Prior studies showed that food insecurity may increase the odds of obesity in children and adults. We still know very little about the familial aggregation of obesity in food insecure households or the mechanisms by which food insecurity confers an increased risk of obesity to children. The purpose of this study was to compare children and mothers from food insecure and food secure households in their weight status, child eating patterns/behaviors, and maternal feeding practices. Design and Methods F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
56
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(65 citation statements)
references
References 63 publications
4
56
0
3
Order By: Relevance
“…In children, studies of food insecurity and weight have reported mixed findings. Some have found positive associations between food insecurity and body weight [ 16 , 41 , 42 ] while others have found none [ 17 , 43 ], or even negative associations [ 44 , 45 ]. Our results suggest that the relationship between food insecurity and child’s overweight may differ by ethnicity.…”
Section: Discussionmentioning
confidence: 99%
“…In children, studies of food insecurity and weight have reported mixed findings. Some have found positive associations between food insecurity and body weight [ 16 , 41 , 42 ] while others have found none [ 17 , 43 ], or even negative associations [ 44 , 45 ]. Our results suggest that the relationship between food insecurity and child’s overweight may differ by ethnicity.…”
Section: Discussionmentioning
confidence: 99%
“…In pregnancy, some aspects of a woman's life may play a major role during the gestational period and for neonatal outcomes, especially in adverse social contexts [10,11]; such effects were estimated to occur for approximately 70% of pregnant women in Nigeria [12] In this sense, FI can be an important variable for the presence or aggravation of stressful pregnancy events by compromising access to sufficient and quality food, as well as increasing clinical complications during pregnancy and childbirth and in newborns [8,13,14]. Some relationships of FI with pregnancy have been documented in previous studies, such as associations of FI with overweight in mothers [5], low birth weight [15], low weight in children, inadequate development, overweight, impaired cognitive development, and behavioural and emotional factors [16][17][18][19].…”
Section: Introductionmentioning
confidence: 98%
“…The strong influence of parental eating behaviour and feeding practices on children's diet is well established [6,13]. However, there is less understanding of parental influences, specifically on children's snacking behaviours [14,15], i.e., energy consumption between meals, particularly in relation to how different healthy or unhealthy snacking habits, might contribute to children's risk of obesity [16]. A recent systematic review of 47 studies on parenting practices that included information on children's snacking found that 39 of these studies concerned parenting practices not specifically related to snacking [17].…”
Section: Introductionmentioning
confidence: 99%